The impact of konjac glucomannan on the physical and chemical stability of walnut oil‐in‐water emulsions coated by whey proteins. (20th January 2022) - Tian, Li; Zhang, Shulin; Yi, Jianhua; Zhu, Zhenbao; Decker, Eric Andrew; McClements, David Julian
Abstract: BACKGROUND: Walnut oil, which is rich in polyunsaturated fatty acids (PUFAs), can be incorporated into food emulsions to increase their nutritional value. However, these emulsions are highly susceptible to deterioration during storage due to lipid oxidation. Konjac glucomannan (KGM) is a neutral plant polysaccharide used as a stabilizer, thickener or gelling agent in foods. The goal of this study was to incorporate KGM into oil‐in‐water emulsions containing walnut oil droplets coated by whey protein isolate (WPI) and then determine its effects on their physical and oxidative stability. RESULTS: At pH 3, inclusion of KGM (0.1–1 g kg −1 ) reduced the positive surface potential on the droplets in the emulsions and modified the secondary structure of the adsorbed whey proteins, suggesting an interaction between KGM and WPI at the droplet surfaces. The physical stability of the emulsions was enhanced when 0.1–0.6 g kg −1 KGM was added but reduced at higher levels. Lipid oxidation was inhibited in the emulsions in a dose‐dependent manner when 0.2–0.6 g kg −1 KGM was added but protein oxidation was promoted at higher KGM levels. The steric hindrance provided by the thick WPI–KGM interfaces, as well as the ability of the polysaccharides to modify the antioxidant properties of the adsorbed proteins, may account for these effects. CONCLUSION: These results suggest that KGM can be used to inhibit lipid oxidation in emulsified foods containing protein‐coated oil droplets. However, its level must be optimized because higher doses can result in droplet aggregation and protein oxidation. © 2022 Society of Chemical Industry.